IMPLEMENTASI PEMBINAAN NARAPIDANA RESIDIVIS DI LEMBAGA PEMASYARAKATAN KELAS IIA KABUPATEN BENGKALIS (PERIODE TAHUN 2019-2021) - Saraswati Aji Sawitri; Elmayanti Elmayanti; Tengku Arif Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Recidivis exists in the case that a person has committed several acts, each of which is anindependent crime, among which one or more acts have been sentenced by a court. Specialtreatment needs to be given because of the special needs of the risks attached to him, but inpractice the Bengkalis Regency Penitentiary does not differentiate between recidivist inmates andnon-recidivist inmates. Therefore, the purpose of this thesis research is first, to find out theimplementation of coaching recidivist prisoners in Bengkalis Prison. Second, find out what effortshave been made by the Bengkalis Prison in fostering recidivist prisoners.This type of research can be classified into the type of sociological juridical legalresearch. This study uses primary data and secondary data consisting of primary legal materials,secondary legal materials, tertiary legal materials, and data collection techniques are carried outby interviewing and distributing questionnaires.From the results of this study there are two main things that can be concluded. First,there is no difference in the form of coaching given by officers to recidivist prisoners and non-recidivist prisoners. There are 2 types of coaching given, namely personality coaching andindependence coaching. Second, the efforts made by the Bengkalis Penitentiary for thedevelopment of recidivist convicts are to emphasize religious activities and also add facilities andinfrastructure for the continued development of convicts so that they are carried out optimally.The author's suggestion is First, the implementation of coaching given to convicts shouldhave a difference between recidivist convicts and non-recidivist convicts. Second, obstacles thatmake the implementation of coaching in the Bengkalis Regency Penitentiary less effective so thatthey can be dealt with immediately.Keywords: Coaching, Prisoner, Recidivist, Penitentiary